Effects of a resistance training intervention on the strength-deficit of elite young soccer players - Irineu Loturco; Lucas A. Pereira; Chris Bishop; Vinicius Zanetti; Tomás T. Freitas; Fernando Pareja-Blanco (Termedia Publishing House, 2021)
The aim of this study was to examine the effects of a traditional resistance training scheme on the relative strength (RS), relative peak-force (RPF), strength deficit (SDef), and vertical jump and sprint abilities in elite young soccer players. Thirty-five under-20 soccer players from two professional clubs were assessed before and after a 4-week competitive period. One team performed 12 sessions of a structured resistance training program and the other maintained their regular soccer-specific training and competitive routines. Resistance training sessions consisted of half-squat and jump-squat exercises at intensities of 30-80% of the one-repetition maximum. Both teams performed pre- and post-measurements in the following order: (1) countermovement jump (CMJ), (2) 20-m sprint, and (3) half-squat one-repetition maximum to determine the RS, RPF, and SDef. A two-way analysis of variance was used to test for group x time interaction among variables. Effect sizes (ES) and 95% confidence intervals (CI) were also calculated. Group x time interactions were demonstrated for RS ([ES [95%CI] = 1.21 [0.57; 1.85], P = 0.001), RPF (ES [95%CI] = 1.18 [0.52; 1.80], P = 0.001), SDef (ES [95%CI] = 0.86 [0.01; 1.71], P = 0.04), and CMJ (ES [95%CI] = 0.64 [0.28; 0.99], P  =  0.001); whereas a  non-significant interaction was observed for 20-m sprint performance (ES [95%CI] = 0.02 [-0.32; 0.36], P = 0.85). Traditional strength-power oriented training resulted in improved maximum strength performance and CMJ ability but, paradoxically, increased the SDef. As a consequence, stronger athletes are not necessarily able to use greater percentages of their peak-force against relatively lighter loads.